(untitled) ("Conference on Universal Science Research 2023", 2024)
The complex nature of msectionedical decision making in cases of disproportionality is demonstrated. Methods available to treat disproportionality have included cesarean section, cranial trepanation, forceps, induction of preterm labor, symphysiotomy, and inversion.Identifying women at risk for developing breech-head disproportionality will allow physicians to make preparatory and treatment decisions that can minimize maternal and neonatal morbidity.